2016
DOI: 10.3390/ijms17060783
|View full text |Cite
|
Sign up to set email alerts
|

Goldfish Leptin-AI and Leptin-AII: Function and Central Mechanism in Feeding Control

Abstract: In mammals, leptin is a peripheral satiety factor that inhibits feeding by regulating a variety of appetite-related hormones in the brain. However, most of the previous studies examining leptin in fish feeding were performed with mammalian leptins, which share very low sequence homologies with fish leptins. To elucidate the function and mechanism of endogenous fish leptins in feeding regulation, recombinant goldfish leptin-AI and leptin-AII were expressed in methylotrophic yeast and purified by immobilized met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…In contrast, the amino acid sequence homology shared between leptin-AI and leptin-AII are much higher, e.g., 82.0% in common carp 25, and 79.5% in goldfish. Previously studies showed that the anorexigenic effects of goldfish leptin-AI and leptin-AII in were highly comparable 17. Our present study shows that the regulatory modules for goldfish leptin -AI and leptin -AII gene expression are also similar.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In contrast, the amino acid sequence homology shared between leptin-AI and leptin-AII are much higher, e.g., 82.0% in common carp 25, and 79.5% in goldfish. Previously studies showed that the anorexigenic effects of goldfish leptin-AI and leptin-AII in were highly comparable 17. Our present study shows that the regulatory modules for goldfish leptin -AI and leptin -AII gene expression are also similar.…”
Section: Discussionsupporting
confidence: 72%
“…The anorexigenic effects of leptin have been described in teleost fish 17, 18 as well as in mammals 19. The nutritional status is shown highly correlated to leptin levels in fish but controversial between different species 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In goldfish, leptin injections decrease feeding and locomotor behavior (Volkoff et al, 2003; de Pedro et al, 2006; Vivas et al, 2011; Tinoco et al, 2012) in part by stimulating anorexigenic sytems (e.g., CART, CCK, and POMC) and inhibiting orexigenic ones (e.g., orexin, NPY, AgRP) (Volkoff et al, 2003; Yan et al, 2016). Similarly, in rainbow trout (Salmoniforme), central leptin administration suppresses food intake and increases the hypothalamic expressions of CART and POMC (Gong et al, 2016).…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…On the other hand, leptin is a peripheral satiety factor that is mainly produced in the adipose tissue of mammals or the liver of fish [41,42]. In goldfish, leptin inhibits appetite by suppressing food intake and feeding behavior [43]. Leptins further regulate the expression of brain neuropeptides [43] and pituitary hormones [44] in goldfish.…”
Section: Discussionmentioning
confidence: 99%